Effect of stoking density on the productivity parameters of young-of-the-year tench (Tinca tinca Linnaeus, 1758) grown in recirculation aquaculture system conditions - R. Konopelsky; H. Kurinenko; I. Hrystyniak; M. Korilyak (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To characterize the productive and biological features of juvenile tench (Tinca tinca Linnaeus, 1758) grown in a recirculation aquaculture system and to select the optimal stocking density for intensive cultivation technology.